CODE MIXING ON THE DIALOGUE OF “9MM” MOBILE GAME BY GAMELOFT - PRATAMA, YONATHAN WAHYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Code, Codes Mixing, Gameloft, 9mm Bilingual people mix their language from one language to another regardless of the topic and place. They do code mixing not only in everyday life, but is now also grown in some video games. This study aimed to investigate the code mixing used by all of the characters in "9mm". "9mm" is the title of a video game that was released for mobile phones. This study is to identify the types of code mixing used by all of the characters in "9mm".This research used theory by Hoffman because this theory has an adequateexplanation and details about the types of code mixing. Thus, there are 4 types of mixed code: 1) intra-sentential switching / code mixing, 2) intra-lexical code mixing, 3) making emblematic, 4) involving a change of pronunciation.There are several steps taken in processing and analyzing the data, by collecting all the data based on the characters in the game, then the data is classified according to the type and cause, and then identified the data or performs the categorization of data and provided a brief description of each data sample. The analysis focused on the type and cause of the events that occurred in the code mixing in the "9mm". Based on the results of the data analysis, it was concluded that the developers of the game "9mm", Gameloft usingEnglish as the primary language used by the characters. Data collection was done by downloading the game "9mm" from Google Play Store, copy words that appear throughout the game, identify and mark utterances that experienced code mixing from English to Spanish.From the research, the authors found four types of mixing languages in the game, namely intra-sentential switching / code mixing, intra-lexical code mixing, making emblematic and involving a change of pronunciation. Types of events over the code and the most dominant code mixing is a type of intra sentential code switching / mixing because the game "9mm" There are a lot of speech interspersed with words in Spanish. In addition there are several causes of the code mixing events, and the most dominant is expressing group identity. This is because most of the characters portrayed in this game live in communities Latin American drug cartels so they get used to mix English and Spanish in their daily conversations.The writer suggests the Sociolinguistics students analyze the reason of codemixing. It is also suggested that the results of this study be used as reference for the future researchers in exploring and expanding the investigation of some other phenomena of code mixing in a video game.